An inexpensive, specific and highly sensitive protocol to detect the Braf(V600E) mutation in melanoma tumor biopsies and blood - Panka, David J (2010)
The Braf(V600E) mutation has been detected in patients with metastatic melanoma, colon, thyroid and other cancer. Recent studies suggested that tumors with this mutation are especially sensitive to Braf inhibitors-hence the need to reliably determine the Braf status of tumor specimens. The present technologies used to screen for this mutation fail to address the problems associated with infiltrating stromal and immune cells bearing wild type Braf alleles and thus may fail to detect the presence of mutant Braf(V600E) tumors. We have developed a rapid, inexpensive method that reduces the contamination of wild type Braf sequences from tumor biopsies. The protocol involves a series of PCR amplifications and restriction digestions that take advantage of unique features of both wild type and mutant Braf RNA at position 600. Using this protocol, mutant Braf can be detected in RNA from mixed populations with as few as 0.1% Braf(V600E) mutant cells.